Factores críticos que ha atravesado el Mercosur en su proceso de integración: una perspectiva desde el ámbito político - Valverde Chaves, Jeannette (2014)
Throughout its 20 years of existence, Mercosur has promoted democratization, peace and stability of its members and sought political dialogue and consolidated senior internal and international cooperation. However, since the last Regional Strategy Paper 2002, Block has faced critical factors in politics that have prevented progress toward the realization of a specific customs union and a common market structured.